Plasmodium falciparum Molecular Chaperones: Guardians of the Malaria Parasite Proteome and Renovators of the Host Proteome - Blatch, Gregory L. (Frontiers in Cell and Developmental Biology, 2022)
Plasmodium falciparum is a unicellular protozoan parasite and causative agent of the most severe form of malaria in humans. The malaria parasite has had to develop sophisticated mechanisms to preserve its proteome under the changing stressful conditions it confronts, particularly when it invades host erythrocytes. Heat shock proteins, especially those that function as molecular chaperones, play a key role in protein homeostasis (proteostasis) of P. falciparum. Soon after invading erythrocytes, the malaria parasite exports a large number of proteins including chaperones, which are responsible for remodeling the infected erythrocyte to enable its survival and pathogenesis. The infected host cell has parasite-resident and erythrocyte-resident chaperones, which appear to play a vital role in the folding and functioning of P. falciparum proteins and potentially host proteins. This review critiques the current understanding of how the major chaperones, particularly the Hsp70 and Hsp40 (or J domain proteins, JDPs) families, contribute to proteostasis of the malaria parasite-infected erythrocytes.